X-ray insights into star and planet formation - Feigelson, Eric D. (National Academy of Sciences, 2010)
Although stars and planets form in cold environments, X-rays are produced in abundance by young stars. This review examines the implications of stellar X-rays for star and planet formation studies, highlighting the contributions of NASA’s (National Aeronautics and Space Administration) Chandra X-ray Observatory. Seven topics are covered: X-rays from protostellar outflow shocks, X-rays from the youngest protostars, the stellar initial mass function, the structure of young stellar clusters, the fate of massive stellar winds, X-ray irradiation of protoplanetary disks, and X-ray flare effects on ancient meteorites. Chandra observations of star-forming regions often show dramatic star clusters, powerful magnetic reconnection flares, and parsec-scale diffuse plasma. X-ray selected samples of premain sequence stars significantly advance studies of star cluster formation, the stellar initial mass function, triggered star-formation processes, and protoplanetary disk evolution. Although X-rays themselves may not play a critical role in the physics of star formation, they likely have important effects on protoplanetary disks by heating and ionizing disk gases.